GE_GERICHTE P/24245/2017 vom 30. November 2018 - GE Cour de justice (2018)
CONTRAINTE(DROIT PÉNAL) ; COMMANDEMENT DE PAYER ; DIFFAMATION ; CALOMNIE ; REPRÉSENTATION ; SIGNATURE COLLECTIVE | CP.173; CP.174; CP.181; CP.52; CPP.310; CPP.8; CO.38